A Love Letter to Those Who Cannot Say “I Love You:” Ada Limón and the Deconstruction of Gender Roles in Favor of Masculine Love - Jones, Harrison (Kansas State University. Dept. of English, 2025)
An exploration of how men love using Ada Limón's poem "Accident Report in the Tall, Tall Weeds." I aim to look at how society has forced men to only express love silently or violently. The article looks into how we as a society have gotten to this point with our men, and how our literature may reinforce or deconstruct this narrative and gender stereotype we have put in place. The purpose of this being to see how we can change this for the future, so the men in our lives are able to properly express love.
Kirmser Undergraduate Research Award - Individual Freshman category, honorable mention
Keywords: Ada Limón; Accident Report in the Tall, Tall Weeds poem; Male Expression of Love; Male Gender Stereotypes; Stereotypes in Gender